Nanoscale control of surface immobilized BMP-2: toward a quantitative assessment of BMP-mediated signaling vents - Baha-Schwab, Elisabeth H.; Pohl, Theresa Lucie Maria; Haraszti, Tamás; Schwaerzer, Gerburg K.; Hiepen, Christian; Spatz, Joachim P.; Knaus, Petra; Cavalcanti-Adam, Elisabetta A. (Nano letters, 2015)
In this work we determine the impact of surface density of immobilized BMP-2 on intracellular signal transduction. We use block copolymer micellar nanolithography to fabricate substrates with precisely spaced and tunable gold nanoparticle arrays carrying single BMP-2 molecules. We found that the immobilized growth factor triggers prolonged and elevated Smad signaling pathway activation compared to the same amount of soluble protein. This approach is suitable for achieving controlled and sustained local delivery of BMP-2 and other growth factors.